The Impact of Bio-Stimulants on Cd-Stressed Wheat (Triticum aestivum L.): Insights Into Growth, Chlorophyll Fluorescence, Cd Accumulation, and Osmolyte Regulation - Farhat, Fozia; Arfan, Muhammad; Wang, Xiukang; Tariq, Arneeb; Kamran, Muhammad; Tabassum, Hafiza Naila; Tariq, Ifra; Mora-Poblete, Freddy; Iqbal, Rashid; El-Sabrout, Ahmed M.; Elansary, Hosam O. (Frontiers in Plant Science, 2022)
Cadmium (Cd) has been recognized as a prominent pollutant affecting human health adversely via the food chain. A pot trial was performed on Cd-stressed wheat seedlings to evaluate the morphological and physio-biochemical responses via foliage spray of two different bio-stimulants i.e., ascorbic acid (AsA) and moringa leaf extract (MLE). Two wheat cultivars (Fsd-08 and Glxy-13) were exposed to Cd stress (0µM, 500µM, and 1000µM) at the three-leaf stage along with foliar spray of AsA (0mM and 50mM) and MLE (0% and 3%). The Cd stress was established in the rhizosphere by dissolving CdCl2.5H2O in a half-strength Hoagland nutrient medium. The most observable growth reduction was documented in plants exposed to the higher Cd concentration (1000 μM) followed by the lower Cd level (500 μM). The wheat growth attributes such as number of leaves per plant, number of tiller per plant, biomass yield, shoot/root length, and leaf area were greatly depressed under Cd stress, irrespective of the cultivar. Under the increasing Cd stress, a significant diminution was observed in maximum photochemical efficiency (Fv/Fm), photochemical quenching (qP), and electron transport rate (ETR) accompanied with reduced gas exchange attributes. However, Cd-induced phytotoxicity enhanced the non-photochemical quenching (NPQ) and internal carbon dioxide concentration (Ci) which was confirmed by their significant positive correlation with Cd contents in shoot and root tissues of both cultivars. The contents of proline, AsA, glycine betaine (GB), tocopherol, total free amino acid (TFAA), and total soluble sugar (TSS) were greatly decreased with Cd (1000 µM), while MLE and AsA significantly enhanced the osmolytes accumulation under the Cd stress (especially 500 µM level). The Cd accumulation was predominantly found in the root as compared to shoots in both cultivars, which was declined after the application of MLE and AsA. Conclusively, aqueous extract of moringa leaves (MLE) was found to be more effective to mitigate Cd-induced phytotoxicity up to 500 µM concentration, compared with the AsA amendment.